Effect of parameters of Nd YAG laser welding on AISI 316 Stainless steel and Brass. (December 2018) - Bhatt, Dhruv; Goyal, Ashish
Abstract: Aspect Ratio (Depth/Width) is one of the most important factor to determine the quality of weld. For a weld to be a perfect one the Aspect Ratio should be maximum. Hence to get a perfect weld one has to ensure that the depth of penetration is good enough. In the current study we are optimizing the Nd-YAG welding system parameters (i.e. like laser peak power, pulse energy, welding speed, frequency) to get the best results on Brass and SS-316LN. Stainless Steel is one of the most widely used material at industry level and brass is already widely used in bearings, ammunition casing and for some electrical appliances. In this experiment the welding is being performed using TRUMPH HL- 506P Nd-YAG Laser Welding System and the welding speed is determined using a rotating mechanism to rotate the rod. The welds were inspected using metallography experiment and metallograph results were used to determine the Aspect Ratio. Based on those results the experiment was successfully concluded.